A CLINICAL STUDY TO EVALUATE ROLE OF AYURVEDIC MANAGEMENT FOR IMPROVING ACTIVITIES OF DAILY LIVING IN CEREBRAL PALSY AFFECTED CHILDREN - Kuldeep R, Choudhary; Kumar, Abhimanyu (International Journal of Ayurveda and Pharma Research, 2015)
Background: Cerebral palsy is disorder of neuromotor origin due to non progressive brain damage in its early developing period. It is often accompanied by other features like seizures, behavioral disorders and cognitive impairment restricting their normal activities of daily living, making them to be dependent on others. Aim and Objectives: The present clinical study was designed with an aim to improve quality of life and establish optimal independence in activities of daily living (ADL) by potentiating the effects of world widely accepted Physiotherapy treatment along with Ayurvedic modality for better management of Cerebral palsy with a ray of new hope. Material and Methods: The study was performed on forty five patients of age group one to twelve years of either sex. Patients were therapeutically randomized into three groups and received treatment for six months. Group A (n=14) received Physiotherapy; Group B (n=14) was treated with Physiotherapy and Ayurvedic procedures while Group C (n=14) received Physiotherapy, Ayurvedic procedures and Syp. Ayurvedic compound. Out of forty five cases, three of them discontinued treatment. Parameters for assessment were based on standard guidelines of Activities of daily living Modified Barthel score. Results: The effect of therapy observed on total ADL score at end of six months was statistically significant (p<0.05) in Group A with a gain of 58.41% while in Group B and C it was statically highly significant (p<0.001) with gain of 62.80% and 62.68% respectively. Conclusion: The improvement noted in Group B and C was enhanced by effects of Ayurvedic procedures and Syp. Ayurvedic compound due to improvement in muscle tone, gain in muscle strength, proper nourishment of Dhatus and intelligence for better skilled performance.